Addressing the efficiency of X-ray protective eyewear: Proposal for the introduction of a new comprehensive parameter, the Eye Protection Effectiveness (EPE). (February 2020) - Doria, S.; Fedeli, L.; Redapi, L.; Piffer, S.; Rossi, F.; Falivene, A.; Busoni, S.; Belli, G.; Gori, C.; Taddeucci, A.
Highlights: Characterization of eye lens X-ray protection efficacy of different eyewear models. Study of the influence of eyewear shape and ergonomics. Combination of dosimetric measurements and geometrical modeling. Introduction of the concept of Eye Protection Effectiveness, an "a priori" evaluation of the Dose Reduction Factor. Abstract: Radioprotection of the eye lens of medical staff involved in Surgical procedures is a subject of international debates since ICRP recommended, on 2011, a lower equivalent dose limit for the lens of the eye. In this work we address the effectiveness of different models of X-ray protective eyewear by relating actual dosimetry measurements to an ad hoc developed mathematical model, in order to disentangle the contribution of geometrical factors and shield capabilities. Phantom irradiation was carried out in fixed exposure conditions in angiographic room: we found that measured Dose Reduction Factors (DRF) strongly depend on the ergonomics of the investigated eyewear. Actually a very poor DRF was observed in the case of a glass model in spite of its high nominal attenuation, whereas a protective tool with low shielding capabilities such a visor resulted much more effective as a consequence of is shape (i.e. extended geometric protection of the eye lens). Our work highlights the need of the introduction of a specific parameter to quantify the effectiveness of the protection tools and able to predict their DRF by taking into account the geometry of the clinical condition of exposure. Aiming at making steps forward the standardization of the guidelines concerning the features of eye protective tools, we developed a simple mathematical model describing the eye lens irradiation geometry which allows the introduction, for each eyewear, of a comprehensive parameter, the Eye Protection Effectiveness (EPE), that, for any defined clinical irradiation condition and glass shielding capabilities and shape, defines the overall effective X-ray protection of the eyewear.